The electronic structure of iridium and its oxides. (28th December 2015) - Pfeifer, Verena; Jones, Travis E.; Velasco Vélez, Juan J.; Massué, Cyriac; Arrigo, Rosa; Teschner, Detre; Girgsdies, Frank; Scherzer, Michael; Greiner, Mark T.; Allan, Jasmin; Hashagen, Maike; Weinberg, Gisela; et al.
Abstract : Iridium‐based materials are among the most active and stable electrocatalysts for the oxygen evolution reaction. Amorphous iridium oxide structures are found to be more active than their crystalline counterparts. Herein, we combine synchrotron‐based X‐ray photoemission and absorption spectroscopies with theoretical calculations to investigate the electronic structure of Ir metal, rutile‐type IrO2, and an amorphous IrOx . Theory and experiment show that while the Ir 4f line shape of Ir metal is well described by a simple Doniach–Šunjić function, the peculiar line shape of rutile‐type IrO2 requires the addition of a shake‐up satellite 1 eV above the main line. In the catalytically more active amorphous IrOx, we find that additional intensity appears in the Ir 4f spectrum at higher binding energy when compared with rutile‐type IrO2 along with a pre‐edge feature in the O K‐edge. We identify these additional features as electronic defects in the anionic and cationic frameworks, namely, formally O I− and Ir III, which may explain the increased activity of amorphous IrOx electrocatalysts. We corroborate our findings by in situ X‐ray diffraction as well as in situ X‐ray photoemission and absorption spectroscopies. Copyright © 2015 John Wiley & Sons, Ltd.